A Multi-ingredient Supplement Reduced Markers of Muscle Damage after a Rugby Match in Collegiate Male Players - Chang-Li Hsueh; Wang-Shiang Huang; Chen-Kang Chang (Journal of Physiological Investigation)
Eccentric exercise and collisions that lead to muscle damage are common place among athletes. This study aimed to investigate the effect of a multi-ingredient supplement (MIS), containing the extracts of turmeric, chicken meat, and apple and ancient peat, on markers of muscle damage in collegiate male players following a rugby match. A position-matched, double-blind, randomized, and crossover design was employed in this study. Each trial consisted of a 14-day supplementation period, followed by a 15-a-side rugby match. A total of 13 participants, eight forward and five backs, with a mean height of 1.76 ± 0.08 m and a mean weight of 86.0 ± 22.8 kg, were included. Blood samples were collected before, immediately, 24 h, and 48 h after the match. Both the MIS (P < 0.001, d = 1.86) and placebo trials (P = 0.002, d = 1.97) exhibited a significant increase in plasma creatine kinase and lactate dehydrogenase (LDH) concentrations from the baseline immediately after the match. However, plasma creatine kinase concentration in the MIS trial was significantly lower at 24 h postmatch compared to the placebo trial (P = 0.029, d = 0.90). Moreover, plasma LDH concentration returned to the baseline level 24 h after the match in the MIS trial, while it remained elevated in the placebo trial (P = 0.001, d = 1.07). In either trials, the plasma tumor necrosis factor-α and malondialdehyde concentrations were not significantly different. In conclusion, the MIS can alleviate muscle damage markers after a rugby match without changes in inflammation and oxidative stress markers.